(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
During research, children with the different age groups were examined, to be able to find appropriate treatment in the future for each category and had a research about the overall image of the frequency of pharmacoresistant forms of epilepsy and types of convulsions.